1997
DOI: 10.1203/00006450-199704000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Adaptation of Isoprenoid Biosynthesis and the LDL Receptor Pathway in Fibroblasts from Patients with Mevalonate Kinase Deficiency

Abstract: In a search for the pathophysiologic mechanisms, we estimated isoprenoid synthesis and concentration, cellular growth, and the activity of the LDL receptor pathway in fibroblasts from patients with mevalonate kinase deficiency (MKD), a severe multisystemic disorder of cholesterol and non-sterol isoprenoid biosynthesis. In response to different concentrations of LDL and non-lipoprotein-bound cholesterol, MKD cells partially counteracted their enzyme defect by increased activities of 3-hydroxy-3-methylglutaryl (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…These patients are characterized by mevalonic aciduria and a broad range of phenotypic findings, including malformations of the central nervous system, facial dysmorphy, psychomotor retardation, and recurrent fever episodes. Plasma cholesterol levels are normal in subjects with mevalonate kinase deficiency, suggesting that compensatory mechanisms, such as increased activities of HMG-CoA reductase and the LDL receptor pathway (50), are sufficient to overcome the enzyme deficiency and provide adequate synthesis of cholesterol as well as non-sterol intermediates for embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are characterized by mevalonic aciduria and a broad range of phenotypic findings, including malformations of the central nervous system, facial dysmorphy, psychomotor retardation, and recurrent fever episodes. Plasma cholesterol levels are normal in subjects with mevalonate kinase deficiency, suggesting that compensatory mechanisms, such as increased activities of HMG-CoA reductase and the LDL receptor pathway (50), are sufficient to overcome the enzyme deficiency and provide adequate synthesis of cholesterol as well as non-sterol intermediates for embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that MA fibroblasts are able to compensate for their defect in MK and that the flux through the cholesterol biosynthesis pathway may be rather normal. This is due to increased activity of HMG-CoA reductase and the LDL receptor pathway in such cells (19,20). It has been reported that this increased activity of HMG-CoA reductase is insuppressible by exogenous LDL cholesterol and can be up-regulated further under cholesterol-free culture conditions (19).…”
mentioning
confidence: 99%
“…Intriguingly, MK enzyme activity appears to be sensitive to temperature, with lower enzyme activity measured in vitro when cells are incubated at higher temperatures (73). There is no absolute deficiency of any of the isoprenoid end-products, although in mevalonic aciduria there is a slight decrease in cholesterol, dolichol, and ubiquinone-10 (72,74,78,80). The mutated MK still responds to feedback regulation by SREBPs (97,126).…”
Section: Review Of Pathophysiology Per Syndromementioning
confidence: 92%